University students’ acceptance and feedback for online delivery learning during the COVID-19 Pandemic Period - Lau, Sian Lun *; Sim, Tze Ying * (2020)
The year 2020 has started with the COVID-19 pandemic. This has caused education institutions around the globe to resort to online teaching and learning delivery in order to ensure safety while not to stop learning progress. It will be interesting to learn whether students are ready and willing to adopt this change, especially when the decision and the change were made within a very short period of time. This paper presents a study carried out across two semester an a private university in Malaysia to investigate students learning experience and factors that may influence it. Both quantitative and qualitative questions were given to over 400 students in each semesters to obtain their feedback. Statistical and sentiment analysis have been carried out to analyse and observe the produced results.